Variability in Test Interval Is Linked to Glycated Haemoglobin (HbA1c) Trajectory over Time. (16th May 2022) - Fryer, Anthony A.; Holland, David; Stedman, Michael; Duff, Christopher J.; Green, Lewis; Scargill, Jonathan; Hanna, Fahmy W. F.; Wu, Pensée; Pemberton, R. John; Bloor, Christine; Heald, Adrian H.
Abstract : Aims . We previously showed that the glycated haemoglobin (HbA1c) testing frequency links to diabetes control. Here, we examine the effect of variability in test interval, adjusted for the frequency, on change in HbA1c ( Δ HbA1c). Materials & Methods . HbA1c results were collected on 83, 872 people with HbA1c results at baseline and 5 years (±3 months) later and ≥6 tests during this period. We calculated the standard deviation (SD) of test interval for each individual and examined the link between deciles of SD of the test interval and Δ HbA1c level, stratified by baseline HbA1c. Results. In general, less variability in testing frequency (more consistent monitoring) was associated with better diabetes control. This was most evident with moderately raised baseline HbA1c levels (7.0–9.0% (54–75 mmol/mol)). For example, in those with a starting HbA1c of 7.0–7.5% (54–58 mmol/mol), the lowest SD decile was associated with little change in HbA1c over 5 years, while for those with the highest decile, HbA1c rose by 0.4–0.6% (4–6 mmol/mol; p < 0.0001 ). Multivariate analysis showed that the association was independent of the age/sex/hospital site. Subanalysis suggested that the effect was most pronounced in those aged <65 years with baseline HbA1c of 7.0–7.5% (54–58 mmol/mol). We observed a 6.7-fold variation in the proportion of people in the top-three SD deciles across general practices. Conclusions . These findings indicate that the consistency of testing interval, not the just number of tests/year, is important in maintaining diabetes control, especially in those with moderately raised HbA1c levels. Systems to improve regularity of HbA1c testing are therefore needed, especially given the impact of COVID-19 on diabetes monitoring.